2010
DOI: 10.1186/1471-2164-11-543
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis and comparative genomics of a Giardia intestinalis assemblage E isolate

Abstract: BackgroundGiardia intestinalis is a protozoan parasite that causes diarrhea in a wide range of mammalian species. To further understand the genetic diversity between the Giardia intestinalis species, we have performed genome sequencing and analysis of a wild-type Giardia intestinalis sample from the assemblage E group, isolated from a pig.ResultsWe identified 5012 protein coding genes, the majority of which are conserved compared to the previously sequenced genomes of the WB and GS strains in terms of microsyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
132
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(138 citation statements)
references
References 50 publications
5
132
0
1
Order By: Relevance
“…Here, we demonstrate that these effects are not only isolate specific but also assemblage specific. Indeed, most severe abnormalities after infection with single isolates were observed in epithelia exposed to BAH12c14, a clone with mixed assemblage A and B genotypic characteristics, or in those epithelial monolayers exposed to assemblage E, a genotype believed to infect livestock but not humans (Monis et al, 2009;Jerlstr¨om-Hultqvist et al, 2010). Interestingly, the mono-infection with assemblage E (known to infect livestock) induced more-severe ZO-1 disruptions and apoptosis in the human HCT-8 epithelia than did monoinfections with representatives of human-specific assemblages A or B.…”
mentioning
confidence: 99%
“…Here, we demonstrate that these effects are not only isolate specific but also assemblage specific. Indeed, most severe abnormalities after infection with single isolates were observed in epithelia exposed to BAH12c14, a clone with mixed assemblage A and B genotypic characteristics, or in those epithelial monolayers exposed to assemblage E, a genotype believed to infect livestock but not humans (Monis et al, 2009;Jerlstr¨om-Hultqvist et al, 2010). Interestingly, the mono-infection with assemblage E (known to infect livestock) induced more-severe ZO-1 disruptions and apoptosis in the human HCT-8 epithelia than did monoinfections with representatives of human-specific assemblages A or B.…”
mentioning
confidence: 99%
“…The excavate order Diplomonadida belongs to an undersampled part of eukaryotic diversity, and studies performed so far have indicated substantial diversity within the order, including alternative genetic codes (21), differences in the number of nuclei, and large genomic differences between morphologically similar organisms (2,7,15,30).…”
mentioning
confidence: 99%
“…However, to date, there are only two diplomonads for which transfection systems have been constructed. Giardia intestinalis was the first transfected diplomonad (32), and it is by far the most-studied organism, benefiting from the wealth of genomic information that is available (7,15,24). Spironucleus vortens, the likely cause of the "hole-in-the-head" disease in tropical fish species (26), has been successfully transfected and has many favorable characteristics as a model organism, such as wide temperature tolerance and extremely rapid growth in vitro to high cell densities (6,23,31).…”
mentioning
confidence: 99%
“…To date, the genomes of three Giardia assemblages (genotypes) have been sequenced. Two of these, assemblages A and E, contain extremely low levels of allelic heterozygosity -less than 0.01% (Morrison et al, 2007;Jerlström-Hultqvist et al, 2010). These results are surprising because, in a presumed asexual organism with two independent nuclei, the nuclear genomesand perhaps even homologous chromosomes -would be expected to diverge over time owing to genetic drift (Birky, 2010).…”
Section: Nuclei Are Inherited In Non-identical Pairsmentioning
confidence: 53%
“…1C,D). The genomes of most Giardia isolates contain very low levels of heterozygosity (Morrison et al, 2007;Teodorovic et al, 2007;Lasek-Nesselquist et al, 2009;Jerlström-Hultqvist et al, 2010), suggesting that the two nuclear genomes are able to exchange genetic information during the Giardia life cycle. The Giardia genome also contains seven homologs of meiosis-specific genes: Spo11, Hop1, Dmc1a, Dmc1b, Hop2, Mnd1 and Mer3 (Ramesh et al, 2005;Malik et al, 2008), which in most organisms are expressed only during meiosis and are specifically involved in meiotic homologous recombination.…”
Section: Introductionmentioning
confidence: 99%